2016
DOI: 10.1136/bjophthalmol-2015-308219
|View full text |Cite
|
Sign up to set email alerts
|

One-year interim comparison of canaloplasty in primary open-angle glaucoma following failed filtering surgery with primary canaloplasty

Abstract: ChiCTR-ICR-15005788, Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Canaloplasty and ECT are two representative Ab externo procedures of SC-based glaucoma surgery. Canaloplasty was reported to be a feasible, e cient, and safe candidate for POAG with prior incisional glaucoma surgery with both intact and disrupted SC [9,10] . Circumferential trabeculotomy, either ab interno or ab externo, was also practiced on POAG patients and presented good IOP control [7,8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canaloplasty and ECT are two representative Ab externo procedures of SC-based glaucoma surgery. Canaloplasty was reported to be a feasible, e cient, and safe candidate for POAG with prior incisional glaucoma surgery with both intact and disrupted SC [9,10] . Circumferential trabeculotomy, either ab interno or ab externo, was also practiced on POAG patients and presented good IOP control [7,8] .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that canaloplasty [5,6] and ECT [7,8] provide good IOP reduction with a favorable safety pro le as an initial procedure for POAG. Moreover, canaloplasty is also a candidate for POAG with prior failed ltering surgeries with or without intact schlemm's canal (SC) [9,10] . Recently, a study reported that circumferential trabeculotomy could be a feasible remedy for POAG with failed canaloplasty [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria for this study were: The full details of the surgical procedures were reported previously [9,13] . Brie y, fornix-based conjunctival and scleral aps were made next to the prior incision.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that canaloplasty [5,6] and ECT [7,8] provide good IOP reduction with a favorable safety pro le as an initial procedure for POAG. Moreover, canaloplasty is also a candidate for POAG with prior failed ltering surgeries with or without intact schlemm's canal (SC) [9,10] . Recently, a study reported that circumferential trabeculotomy could be a feasible remedy for POAG with failed incisional glaucoma surgery [11] and failed canaloplasty [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when we perform canaloplasty on patients with POAG with failed trabeculectomy, the microcatheter could be easily inserted around the entire circumference and the postoperative IOP gradually becomes controlled, compared with subjects receiving circumferential trabeculotomy alone. 71,72 This finding indicates that a more collapsed SC, as a result of damage from trabeculectomy, could have a lumen that remains open. The surgical procedure permits drainage of the aqueous humor into SC.…”
Section: New Insights On Scmentioning
confidence: 96%